Effects of flow depth variations on the wake recovery behind a horizontal-axis hydrokinetic in-stream turbine. (September 2018) - Aghsaee, Payam; Markfort, Corey D.
Abstract: In-stream hydrokinetic turbines have the potential to produce a significant amount of clean energy from river and tidal currents. This study investigates for the first time the effects of flow depth on the wake behavior downstream of a horizontal axis hydrokinetic turbine. The far wake velocity deficit did not exhibit the symmetric Gaussian profile often found downstream of wind turbines. The flow confinement in an open channel causes the wake to recover more slowly compared to wind tunnel studies with deeper boundary layers. Our results show that with the same local mean kinetic energy, from which the turbine is able to extract energy, a greater total mean kinetic energy in the flow affects the rate of wake recovery. It is observed that for a deeper flow, the mean velocity recovers more rapidly and the turbulence intensity recovers more slowly. In addition to turbulence intensity and thrust coefficient, the ratio of the flow depth to the turbine diameter ( H / D ) is shown to be an important parameter related to the wake recovery rate. This parameter represents the amount of total incoming mean kinetic energy available for the turbine wake recovery and is much lower for hydrokinetic turbines compared to wind turbines. Highlights: First study of effects of depth variations on wake behavior behind a horizontal-axis hydrokinetic in-stream turbine. Open channel laboratory study using LDV for velocity measurements. The wake recovers more rapidly behind a deeper flow, which is associated with greater mean kinetic energy of the flow. Turbulence intensity recovers more slowly as the flow becomes deeper. The ratio of total depth to turbine diameter can affect the wake recovery.